Reliability of Diagnostic Tests for Helicobacter pylori Infection - S. Redéen; F. Petersson; E. Törnkrantz; H. Levander; E. Mårdh; K. Borch (Gastroenterology Research and Practice)
Introduction. Helicobacter pylori (H. pylori) infection is very common worldwide. A reliable diagnosis is crucial for patients with H. pylori-related diseases. At followup, it is important to confirm that eradication therapy has been successful. There is no established gold standard for the diagnosis of H. pylori infection. Material and Methods. A sample of 304 volunteers from the general population was screened for H. pylori infection with serology, 13C-urea breath test (UBT), rapid urease test (RUT) on fresh biopsy, culture from biopsy, and histological examination. Culture was used as gold standard. Results. The sensitivity was 0.99 for serology, 0.90 for UBT, 0.90 for RUT, and 0.90 for histological examination. Corresponding specificities were 0.82, 0.99, 0.98, and 0.97, respectively. The accuracy was 0.86 for serology, 0.96 for UBT, 0.95 for RUT, 0.93 for culture, and 0.95 for histology. There was a strong correlation between the results of UBT and the histological scores of H. pylori colonisation as well as between the results of UBT and the scores of RUT. Conclusion. There were only minor differences in accuracy between the three invasive tests for H. pylori infection in this population. RUT may be recommended as the first choice since a result is obtained within hours. The accuracy of UBT was comparable to the invasive tests, and it is recommended for situations when endoscopy is not needed.